Legal and administrative aspects of maintaining cleanliness and order in municipalities - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2013)
Maintaining cleanliness and order in municipalities poses a challenge for local governments. In the context of the changing legal and factual contexts they operate in, municipalities are obliged to take action to protect the environment in everything they do. New tasks and challenges for maintaining environmental safety standards can be found at the local level.